Ambient effect on thermal stability of amorphous InGaZnO thin film transistors. (December 2016) - Xu, Jianeng; Wu, Qi; Xu, Ling; Xie, Haiting; Liu, Guochao; Zhang, Lei; Dong, Chengyuan
Highlights: Air could apparently improve the thermal stability of the a-IGZO TFTs. The ambient oxygen was proved to exhibit the evident improvements in the thermal stability of the a-IGZO TFTs. The negative Vth shifts of the a-IGZO TFTs at high temperatures were hardly influenced by the extra electrons donated by H2 O. The higher ambient oxygen content in the surrounding atmosphere made the thermal generation of the oxygen vacancies in the active layers more difficult. Abstract: The thermal stability of amorphous InGaZnO thin film transistors (a-IGZO TFTs) with various ambient gases was investigated. The a-IGZO TFTs in air were more thermally stable than the devices in the ambient argon. Oxygen, rather than nitrogen and moisture, was responsible for this improvement. Furthermore, the thermal stability of the a-IGZO TFTs improved with the increasing oxygen content in the surrounding atmosphere. The related physical mechanism was examined, indicating that the higher ambient oxygen content induced more combinations of the oxygen vacancies and adsorbed oxygen ions in the a-IGZO, which resulted in the larger defect formation energy. This larger defect formation energy led to the smaller variation in the threshold voltage for the corresponding TFT devices.